Composite current collector, composite pole piece, battery cell, battery monomer, battery and electric device
By using a polymer support layer and conductive layer with specific design of breathability and porosity in lithium-ion secondary batteries, a composite fluid is formed and the positive and negative electrodes are isolated through the composite electrode sheet, the complexity and energy of the traditional battery cell structure are solved. The problem of low density achieves reduced internal resistance and increased energy density.
Patent Information
- Application Number
- CN202411463144.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2022-01-06
- Publication Date
- 2024-12-31
AI Technical Summary
The battery cell structure of traditional lithium-ion secondary batteries is complex and the positive electrode plate and the negative electrode plate are not tight enough, resulting in a decrease in energy density, making it difficult to meet the high requirements of new energy vehicles and energy storage systems for energy density.
The polymer support layer with a breathability of 50 s/100cc~3000 s/100cc and a conductive layer with a porosity of 10%~95% are used to form a composite liquid collector, reduce the volume of the current collector, increase the energy density of the battery, and pass the composite The electrode sheet isolates the positive electrode from the negative electrode, simplifying the battery cell structure.
It has achieved the reduction of the internal resistance of the battery and the improvement of energy density, simplified the cell structure design, improved the cycling performance and energy density of the battery, and met higher usage needs.
Smart Images

Figure CN119230845A_ABST
Abstract
Description
[0001] This application is a divisional application of the invention patent application with the application date of January 6, 2022, application number 202210011783.8, and invention name "Composite current collector, composite electrode, battery cell, battery cell, battery and electrical device". Technical Field
[0002] The present application relates to the field of battery technology, and in particular to a composite current collector, a composite pole piece, a battery cell, a battery cell, a battery and an electrical device. Background Art
[0003] Lithium-ion secondary batteries have many advantages such as high energy density, high power density and long cycle life, and therefore have received widespread attention in the fields of portable electronic devices, new energy vehicles and energy storage batteries.
[0004] The rapid development of new energy vehicles and large-scale energy storage systems has put forward higher requirements on the energy density of lithium-ion secondary batteries. Summary of the invention
[0005] In view of the above requirements, the present application provides a composite current collector and a composite pole piece, which have good cycle performance and can improve the energy density of lithium-ion secondary batteries.
[0006] In addition, a battery cell, a battery cell, a battery and an electrical device using the composite current collector or the composite pole piece are also provided.
[0007] In one aspect, the present application provides a composite current collector comprising:
[0008] A polymer support layer, wherein the air permeability of the polymer support layer is 50 s / 100cc to 3000 s / 100cc; and
[0009] A conductive layer, wherein the conductive layer includes a negative electrode conductive layer and a positive electrode conductive layer;
[0010] The negative electrode conductive layer and the positive electrode conductive layer are respectively disposed on both side surfaces of the polymer support layer; the porosity of the negative electrode conductive layer and the positive electrode conductive layer are independently 10% to 95%;
[0011] The material of the conductive layer is selected from at least one of a metal material, a carbon-based conductive material and a polymer conductive material; the thickness of the negative electrode conductive layer is 200 nm to 3000 nm, and the thickness of the positive electrode conductive layer is 200 nm to 3000 nm.
[0012] In the technical solution in the embodiment of the present application, a polymer support layer with an air permeability of 50 s / 100cc~3000 s / 100cc is used as a substrate, and a positive electrode conductive layer and a negative electrode conductive layer with a porosity of 10%~95% are respectively arranged on the two opposite surfaces thereof to obtain a composite current collector in which the positive electrode current collector and the negative electrode current collector are integrated, thereby reducing the current collector volume and helping to improve the battery energy density. Since the air permeability of the polymer support layer is 50 s / 100cc~3000 s / 100cc and the porosity of the conductive layer is 10%~95%, the ions in the electrolyte can pass through the composite current collector, which helps to reduce the internal resistance of the battery.
[0013] In some embodiments, the air permeability of the polymer support layer is 150 s / 100cc to 1500 s / 100cc.
[0014] In some embodiments, the porosity of the negative electrode conductive layer and the positive electrode conductive layer is independently 30% to 60%.
[0015] In some embodiments, the thickness of the negative electrode conductive layer is 500 nm to 1500 nm;
[0016] And / or, the thickness of the positive electrode conductive layer is 500 nm to 1500 nm. The thickness of the conductive layer can be adjusted according to the battery capacity. The conductive layer in the above thickness range can ensure that the composite current collector has a more suitable battery internal resistance and conductivity.
[0017] In some embodiments, the negative electrode conductive layer and / or the positive electrode conductive layer includes: a functional layer; the thickness of the functional layer is 500 nm to 3000 nm. The function of the functional layer is to provide the conductive layer with suitable conductivity. Controlling the thickness of the functional layer within the above range can provide the composite current collector with suitable conductivity.
[0018] In some embodiments, the negative electrode conductive layer and / or the positive electrode conductive layer further comprises: at least one of a pore-forming transition layer and a thickening layer;
[0019] The thickness of the hole-making transition layer is 2 nm to 100 nm; the thickness of the thickening layer is 5 nm to 300 nm. The function of the hole-making transition layer is to form a regular hole pattern as a template to form a conductive layer with a suitable porosity. The function of the thickening layer is to thicken the conductive layer to provide a suitable resistance. According to the functions of the hole-making transition layer and the thickening layer, their thickness can be optionally set within the above range.
[0020] In some embodiments, the composite current collector further comprises:
[0021] An anti-oxidation layer, the anti-oxidation layer is arranged on the surface of the negative electrode conductive layer and / or the positive electrode conductive layer away from the polymer support layer. The anti-oxidation layer is arranged on the surface of the negative electrode conductive layer and / or the positive electrode conductive layer to prevent the conductive layer from being oxidized. In some embodiments, the material of the anti-oxidation layer is selected from at least one of conductive carbon, metal materials and metal oxides. In some embodiments, the thickness of the anti-oxidation layer is 500 nm to 1500 nm. The anti-oxidation layer in the above thickness range can ensure that the conductive layer does not oxidize and slow down the aging process of the composite current collector.
[0022] In some embodiments, the material of the polymer support layer is selected from at least one of polyamide (PA), polyimide (PI), polyethylene terephthalate (PET), polyethylene (PE), polypropylene (PP), polyvinyl alcohol (PVA), polystyrene (PS) and cellulose. The above polymer materials as the polymer support layer have good thermal stability and mechanical properties.
[0023] In a second aspect, the present application further provides a composite pole piece, comprising:
[0024] The composite current collector in the above embodiment;
[0025] a positive electrode material layer, the positive electrode material layer being disposed on a surface of the positive electrode conductive layer away from the polymer support layer; and
[0026] A negative electrode material layer is provided on a surface of the negative electrode conductive layer away from the polymer support layer.
[0027] The composite electrode sheet including the composite current collector of the above embodiment integrates the positive electrode sheet and the negative electrode sheet into one, and the ions in the electrolyte can pass through the composite current collector and move between the positive electrode material layer and the negative electrode material layer, while isolating the positive electrode material layer from the negative electrode material layer, thereby isolating and protecting the positive and negative electrodes.
[0028] In a third aspect, the present application further provides a battery cell, including:
[0029] The composite pole piece in the above embodiment, and
[0030] Isolation film;
[0031] The battery core is manufactured by a winding process or a lamination process.
[0032] The composite electrode sheet of the battery cell of the above embodiment acts as an isolation membrane because the composite current collector separates the positive electrode material layer and the negative electrode material layer, and the ions in the electrolyte can pass through the composite current collector and move between the positive electrode material layer and the negative electrode material layer. The battery cell has a simple structure, a small internal resistance, and the positive electrode and the negative electrode are integrated into one, so the battery cell has a smaller volume and a higher energy density.
[0033] In a fourth aspect, the present application further provides a battery cell, comprising: a housing and at least one battery cell in the above-mentioned embodiment.
[0034] In a fifth aspect, the present application also provides a battery, including: the battery cell in the above embodiment.
[0035] In a sixth aspect, the present application also provides an electrical device, comprising the battery in the above embodiment.
[0036] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Various other advantages and benefits will become apparent to those of ordinary skill in the art by reading the detailed description of the optional embodiments below. The accompanying drawings are only used for the purpose of illustrating the optional embodiments and are not to be considered as limiting the present application. Moreover, the same reference numerals are used throughout the drawings to represent the same components. In the drawings:
[0038] Figure 1 This is a schematic diagram of the structure of a composite current collector according to an embodiment of the present application;
[0039] Figure 2 This is a schematic diagram of the structure of a composite current collector according to an embodiment of the present application;
[0040] Figure 3 This is a schematic diagram of the structure of a composite current collector according to an embodiment of the present application;
[0041] Figure 4 A schematic diagram of the structure of a composite pole piece according to an embodiment of the present application;
[0042] Figure 5 This is a schematic diagram of the structure of a battery cell according to an embodiment of the present application;
[0043] Figure 6 This is a schematic diagram of the exploded structure of a battery cell according to an embodiment of the present application;
[0044] Figure 7 A schematic diagram of the exploded structure of a battery according to an embodiment of the present application;
[0045] Figure 8 A schematic diagram of the structure of a vehicle according to an embodiment of the present application;
[0046] Figure numerals: 10, composite current collector; 110, polymer support layer; 120, conductive layer; 121, negative electrode conductive layer; 122, positive electrode conductive layer; 130, pore-making transition layer; 140, thickening layer; 150, functional layer; 160, antioxidant layer; 20, composite pole piece; 210, positive electrode material layer; 220, negative electrode material layer; 30, battery cell; 310, isolation membrane; 40, battery cell; 41, end cover; 42, shell; 41a, electrode terminal; 50, battery; 51, casing; 511, first part; 512, second part; 60, vehicle; 61, controller; 62, motor. DETAILED DESCRIPTION
[0047] In order to facilitate the understanding of the present application, the present application will be described more fully below with reference to the relevant drawings. The preferred embodiments of the present application are given in the drawings. However, the present application can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present application more thorough and comprehensive.
[0048] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application. The term "and / or" used herein includes any and all combinations of one or more of the related listed items.
[0049] Lithium-ion secondary batteries are widely used in portable electronic devices, new energy vehicles and energy storage systems. With the development of the new energy industry, the performance of lithium-ion secondary batteries is also facing great challenges.
[0050] Researchers have noticed that conventional lithium-ion secondary battery cells are usually made of a positive electrode sheet, a negative electrode sheet and a separator. On the one hand, the preparation process of the multi-layer winding structure is relatively complicated; on the other hand, the positive electrode sheet, the negative electrode sheet and the separator in the multi-layer winding structure are not tightly bonded, resulting in a decrease in the energy density of the battery.
[0051] Based on the above considerations, it has been found through research that the substrate of the traditional current collector can be replaced with an isolation membrane material commonly used in lithium-ion secondary batteries. The isolation membrane material is a polymer film material with pores. The composite current collector is prepared using the isolation membrane material as a substrate. It can provide a composite current collector that is permeable to electrolyte ions, and can also serve to isolate the positive and negative electrodes. It can simplify the structural design of lithium-ion secondary battery cells and improve the energy density of the cells.
[0052] See also Figure 1 In one embodiment of the present application, a composite current collector 10 is provided, comprising: a polymer support layer 110 and a conductive layer 120 .
[0053] The air permeability of the polymer support layer 110 is 50 s / 100cc to 3000 s / 100cc.
[0054] The conductive layer 120 includes a negative conductive layer 121 and a positive conductive layer 122. The negative conductive layer 121 and the positive conductive layer 122 are respectively disposed on two opposite surfaces of the polymer support layer 110; the porosity of the negative conductive layer 121 and the positive conductive layer 122 is independently 10% to 95%;
[0055] The material of the conductive layer 120 is selected from at least one of a metal material, a carbon-based conductive material and a polymer conductive material; the thickness of the negative electrode conductive layer 121 is 200 nm to 3000 nm, and the thickness of the positive electrode conductive layer 122 is 200 nm to 3000 nm.
[0056] It should be explained that air permeability refers to the permeability of air through fabrics (including traditional textiles and products, non-woven fabrics, blankets, high-permeability paper, filter materials, leather, PE and PTFE films, polyurethane soft foam, various felts, etc.), which is expressed as the rate at which air flows vertically through the sample under the specified sample area, pressure drop and time conditions. Therefore, air permeability represents the amount of air that passes through the material per second. CC is a unit of volume measurement, the full name is cubic centimeter, which refers to cubic centimeters (cm³), and the conversion relationship is 1 cubic meter = 1000 cubic decimeters = 1000000 cubic centimeters.
[0057] Porosity refers to the percentage of the pore volume in the bulk material to the total volume of the material in its natural state. In the embodiment of the present application, the porosity of the negative electrode conductive layer 121 and the positive electrode conductive layer 122 is monitored by a charge-coupled device (CCD).
[0058] It should be noted that the polymer support layer 110 can be a lithium-ion secondary battery separator commonly used in the art that meets the above-mentioned air permeability requirements. The main function of the separator is to separate the cathode and anode (positive electrode, negative electrode) materials of the battery to prevent the two electrodes from contacting and short-circuiting. In addition, during the electrochemical reaction, it can maintain the necessary electrolyte and form a channel for ion movement. Therefore, the separator has a porous structure, high liquid absorption rate, strong mechanical strength, stable electrochemical performance, and can prevent the growth of lithium dendrites; it is suitable as the polymer support layer 110 in the composite current collector 10 of the present application. In some embodiments, the material of the separator can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The separator can be a single-layer film or a multi-layer composite film, without special restrictions. When the separator is a multi-layer composite film, the materials of each layer can be the same or different, without special restrictions. It can be understood that the polymer support layer 110 can also use other materials that meet the air permeability requirements.
[0059] In the technical solution of the embodiment of the present application, a polymer support layer 110 with an air permeability of 50 s / 100cc~3000 s / 100cc is used as a substrate, and a positive electrode conductive layer 122 and a negative electrode conductive layer 121 with a porosity of 10%~95% are respectively arranged on the two opposite surfaces thereof, so as to obtain a composite current collector 10 in which a positive electrode current collector and a negative electrode current collector are integrated, and the conductive layer is made of a specific material and a specific thickness, so that the volume of the current collector can be reduced, which is beneficial to improving the battery energy density. Since the air permeability of the polymer support layer 110 is 50 s / 100cc~3000 s / 100cc, and the porosity of the positive electrode conductive layer 121 and the negative electrode conductive layer 122 are both within the range of 10%~95%, the ions in the electrolyte can pass through the composite current collector 10, which is beneficial to reducing the internal resistance of the battery.
[0060] The polymer support layer 110 needs to ensure that lithium ions in the electrolyte can pass smoothly. In the embodiment of the present application, the air permeability of the polymer support layer 110 is 50 s / 100cc~3000 s / 100cc. If the air permeability of the polymer support layer 110 is too high, the pores of the polymer support layer 110 are equivalent to closed pores, and the lithium ions of the electrolyte cannot pass through, and high ion conductivity cannot be achieved; while if the air permeability is too low, it is equivalent to penetration, and large particle ions of other substances will also pass through, affecting the safety of the current collector. In some embodiments, the air permeability of the polymer support layer 110 is 50 s / 100cc to 300 s / 100cc, 300 s / 100cc to 600 s / 100cc, 600 s / 100cc to 1000 s / 100cc, 1000 s / 100cc to 2000 s / 100cc, or 2000 s / 100cc to 3000 s / 100cc. Further, the air permeability of the polymer support layer 110 is 50 s / 100cc to 300 s / 100cc. By controlling the air permeability of the polymer support layer 110 within this range, it is beneficial to obtain a composite current collector 10 with better energy density and lower internal resistance. Optionally, the air permeability of the polymer support layer 110 is 50 s / 100cc, 60 s / 100cc, 80 s / 100cc, 100 s / 100cc, 120 s / 100cc, 150 s / 100cc, 180 s / 100cc, 200 s / 100cc, 250 s / 100cc or 300 s / 100cc.
[0061] In some embodiments, the material of the polymer support layer 110 is selected from at least one of polyamide (PA), polyimide (PI), polyethylene terephthalate (PET), polyethylene (PE), polypropylene (PP), polyvinyl alcohol (PVA), polystyrene (PS) and cellulose. The polymer support layer 110 made of the above materials has good thermal stability and can improve the safety of the composite current collector.
[0062] The porosity of the conductive layer 120 is also related to the ion conductivity of the composite current collector 10. In the embodiment of the present application, the porosity of the conductive layer 120 is 10% to 95%, and the porosity within this range meets the ion conductivity required for the design. When the porosity is lower than the lower limit, the ion conductivity is insufficient and the ion pass rate decreases; when the porosity is higher than the upper limit, the ions penetrate into the conductive layer 120. In some embodiments, the porosity of the conductive layer 120 is 10% to 50% or 50% to 95%. Further, the porosity of the negative electrode conductive layer 121 is 30% to 60%. The porosity of the positive electrode conductive layer 122 is 30% to 60%. In this range, the composite current collector 10 has a more suitable ion conductivity. Optionally, the porosity of the conductive layer 120 is 30%, 35%, 40%, 45%, 50%, 55% or 60%.
[0063] In some embodiments, the material of the conductive layer 120 is selected from at least one of a metal material, a carbon-based conductive material, and a polymer conductive material. The metal material is selected from at least one of aluminum, aluminum alloy, copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, iron, iron alloy, silver, and silver alloy. The carbon-based conductive material is selected from at least one of graphite, superconducting carbon, acetylene black, carbon black, Ketjen black, carbon nanotubes, carbon dots, graphene, and carbon nanofibers. The polymer conductive material is selected from at least one of polysulfur nitride, aromatic ring conjugated polymer, aliphatic conjugated polymer, and aromatic heterocyclic conjugated polymer.
[0064] Optionally, the material of the negative electrode conductive layer 121 is copper; and the material of the positive electrode conductive layer 122 is aluminum.
[0065] Typically, the thickness of the conductive layer 120 is adjusted according to the battery capacity design. In some embodiments, the thickness of the negative electrode conductive layer 121 is 200 nm to 3000 nm. The thickness of the positive electrode conductive layer 122 is 200 nm to 3000 nm. Further, the thickness of the negative electrode conductive layer 121 is 500 nm to 1500 nm. The thickness of the positive electrode conductive layer 122 is 500 nm to 1500 nm. Within this thickness range, the conductive layer 120 has the best conductivity. Above this thickness, the resistance of the conductive layer 120 increases and the conductivity decreases; below this thickness, although the resistance becomes smaller, the stability of the composite current collector 10 decreases.
[0066] See also Figure 2 In some embodiments, the negative electrode conductive layer 121 and / or the positive electrode conductive layer 122 includes: a pore-forming transition layer 130 , a thickening layer 140 and a functional layer 150 .
[0067] The function of the pore-forming transition layer 130 is to form a regular pore pattern so as to form a conductive layer 120 with a suitable porosity. In some embodiments, the thickness of the pore-forming transition layer 130 is 2 nm to 100 nm. It can be understood that, according to the performance requirements of the composite current collector, in some embodiments, the negative electrode conductive layer 121 and / or the positive electrode conductive layer 122 do not contain the pore-forming transition layer 130.
[0068] The function of the thickening layer 140 is to provide a suitable resistance for thickening the conductive layer 120. In some embodiments, the thickness of the thickening layer 140 is 5 nm to 300 nm. It can be understood that, according to the performance requirements of the composite current collector, in some embodiments, the negative electrode conductive layer 121 and / or the positive electrode conductive layer 122 does not contain the thickening layer 140.
[0069] The function of the functional layer 150 is to provide the conductive layer 120 with appropriate conductivity. The appropriate conductivity can be adjusted by controlling the thickness of the functional layer 150. It is a necessary structure to provide the composite current collector with conductivity. In some embodiments, the thickness of the functional layer 150 is 500 nm to 3000 nm.
[0070] In some embodiments, when the material of the conductive layer 120 is a metal material, the conductive layer 120 is prepared by using at least one of a vapor deposition method, a chemical plating method, and an electroplating method.
[0071] The vapor deposition method may be a physical vapor deposition method (PVD). The physical vapor deposition method is selected from at least one of an evaporation method and a sputtering method. Among them, the evaporation method is selected from at least one of a vacuum evaporation method, a thermal evaporation method, and an electron beam evaporation method (EBEM). The sputtering method may be a magnetron sputtering method.
[0072] In some embodiments, the conductive layer 120 is formed by vacuum evaporation, including: placing the polymer support layer 110 after surface cleaning in a vacuum coating chamber, melting and evaporating the high-purity metal wire in the metal evaporation chamber at a high temperature of 1300° C. to 2000° C., and the evaporated metal passes through a cooling system in the vacuum coating chamber, and finally deposits on the polymer support layer 110 to form the conductive layer 120. By setting a mask with a porous structure on the polymer support layer 110 as a template, the conductive layer 120 with different porosities can be prepared.
[0073] In some embodiments, the hole-forming transition layer 130 , the thickened layer 140 , and the functional layer 150 of the conductive layer 120 can all be prepared by vapor deposition.
[0074] In other embodiments, the pore-forming transition layer 130 in the conductive layer 120 is prepared by vapor deposition to obtain a pore-forming transition layer 130 with suitable porosity. The thickened layer 140 and the functional layer 150 in the conductive layer 120 are prepared by chemical plating or electroplating on the basis of the pore-forming transition layer 130. As an example, the composite current collector 10 of an embodiment can be prepared by the following methods: (1) vacuum evaporation method is used to prepare the pore-forming transition layer 130: the polymer support layer 110 after surface cleaning is placed in a vacuum plating chamber, and the high-purity metal wire in the metal evaporation chamber is melted and evaporated at a high temperature of 1300°C to 2000°C. The evaporated metal passes through the cooling system in the vacuum plating chamber and is finally deposited on one side of the polymer support layer 110 to form a pore-forming transition layer 130 with a suitable porosity; (2) electroplating method is used to prepare the thickening layer 140 and the functional layer 150: the polymer support layer 110 deposited with the pore-forming transition layer 130 is immersed in the electroplating solution, and the metal ions are precipitated using the pore-forming transition layer 130 as a template to form the thickening layer 140 and the functional layer 150.
[0075] See also Figure 3 In some embodiments, the composite current collector 10 further includes an anti-oxidation layer 160. The anti-oxidation layer 160 is disposed on the surface of the conductive layer 120 away from the polymer support layer 110. The anti-oxidation layer 160 is disposed on the surface of the conductive layer 120 to prevent the conductive layer 120 from being oxidized and affecting the conductive performance.
[0076] It can be understood that, according to the difference in redox properties of the negative electrode conductive layer 121 and the positive electrode conductive layer 122 , the anti-oxidation layer 160 can be separately disposed on the surface of the negative electrode conductive layer 121 and / or the positive electrode conductive layer 122 .
[0077] In some embodiments, the material of the anti-oxidation layer 160 is selected from at least one of conductive carbon, metal materials and metal oxides. Optionally, the conductive carbon is selected from at least one of graphite, superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers. The metal material is selected from at least one of nickel, chromium, nickel-based alloys and copper-based alloys. The metal oxide can be at least one of aluminum oxide, chromium oxide, cobalt oxide and nickel oxide.
[0078] In some embodiments, the thickness of the anti-oxidation layer 160 is 500 nm to 1500 nm. Optionally, the thickness of the anti-oxidation layer 160 is 500 nm to 1000 nm or 1000 nm to 1500 nm. Further, the thickness of the anti-oxidation layer 160 is 500 nm, 600 nm, 700 nm, 800 nm, 900 nm, 1000 nm, 1100 nm, 1200 nm, 1300 nm, 1400 nm or 1500 nm.
[0079] See also Figure 4 In another embodiment of the present application, a composite electrode sheet 20 is provided, comprising: the composite current collector 10 in the above embodiment, a positive electrode material layer 210 and a negative electrode material layer 220 .
[0080] The positive electrode material layer 210 is disposed on a surface of the positive electrode conductive layer 122 away from the polymer support layer 110 . The negative electrode material layer 220 is disposed on a surface of the negative electrode conductive layer 121 away from the polymer support layer 110 .
[0081] The composite electrode sheet 20 including the composite current collector 10 of the above-mentioned embodiment integrates the positive electrode sheet and the negative electrode sheet into one, and the ions in the electrolyte can pass through the composite current collector 10 and move between the positive electrode material layer 210 and the negative electrode material layer 220, while isolating the positive electrode material layer 210 from the negative electrode material layer 220, thereby isolating and protecting the positive and negative electrodes.
[0082] In some embodiments, the positive electrode material layer 210 includes: a positive electrode active material, a conductive agent, and a binder.
[0083] The positive electrode active material is an important component in the composite electrode sheet 20 that plays a role in inserting and extracting lithium. In some embodiments, the positive electrode active material may adopt positive electrode active materials for batteries that are well known in the art. As an example, the positive electrode active material may include at least one of the following materials: lithium-containing phosphates with an olivine structure, lithium transition metal oxides, and their respective modified compounds. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Among them, examples of lithium transition metal oxides may include, but are not limited to, lithium cobalt oxides (such as LiCoO 2 ), lithium nickel oxide (such as LiNiO 2 ), lithium manganese oxide (such as LiMnO 2 、LiMn 2 O 4 ), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (such as LiNi 1 / 3 Co 1 / 3 Mn1 / 3 O 2 (Also referred to as NCM 333 )、LiNi 0.5 Co 0.2 Mn 0.3 O 2 (Also referred to as NCM 523 )、LiNi 0.5 Co 0.25 Mn 0.25 O 2 (Also referred to as NCM 211 )、LiNi 0.6 Co 0.2 Mn 0.2 O 2 (Also referred to as NCM 622 )、LiNi 0.8 Co 0.1 Mn 0.1 O 2 (Also referred to as NCM 811 ), lithium nickel cobalt aluminum oxide (such as LiNi 0.85 Co 0.15 Al 0.05 O 2 ) and its modified compounds, etc. Examples of lithium-containing phosphates with olivine structure may include but are not limited to lithium iron phosphate (such as LiFePO 4 (also referred to as LFP), composite materials of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO 4 ), at least one of a composite material of lithium manganese phosphate and carbon, a composite material of lithium iron manganese phosphate, and a composite material of lithium iron manganese phosphate and carbon.
[0084] The conductive agent can improve the conductivity of the active material layer and improve the charge and discharge performance of the composite electrode 20. In some embodiments, the conductive agent can be selected from but not limited to at least one of superconducting carbon, conductive graphite, acetylene black, carbon nanotubes, carbon black, and graphene.
[0085] The binder in the positive electrode material layer 210 is generally a hydrophobic binder. In some embodiments, the binder may be selected from, but not limited to, at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.
[0086] In some embodiments, the positive electrode material layer 210 can be prepared in the following manner: the components for the positive electrode material layer 210, such as the positive electrode active material, the conductive agent, the binder and any other components, are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on one side of the composite current collector 10 close to the positive electrode conductive layer 122, and after drying, cold pressing and other processes, the positive electrode material layer 210 can be obtained.
[0087] In some embodiments, the negative electrode material layer 220 includes: a negative electrode active material, a conductive agent, and a binder.
[0088] In some embodiments, the negative electrode active material may adopt the negative electrode active material for batteries known in the art. As an example, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc. The silicon-based material may be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxide compounds, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.
[0089] The binder in the negative electrode material layer 220 is generally a hydrophilic binder. In some embodiments, the binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).
[0090] In some embodiments, the conductive agent in the negative electrode material layer 220 may be selected from but not limited to at least one of superconducting carbon, conductive graphite, acetylene black, carbon nanotubes, carbon black, and graphene.
[0091] In some embodiments, the negative electrode material layer 220 may further include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).
[0092] In some embodiments, the negative electrode material layer 220 can be prepared in the following manner: the components of the negative electrode material layer 220, such as the negative electrode active material, the conductive agent, the binder and any other components, are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on one side of the composite current collector 10 close to the negative electrode conductive layer 121, and after drying, cold pressing and other processes, the negative electrode material layer 220 can be obtained.
[0093] See also Figure 5In another embodiment of the present application, a battery cell 30 is provided, which includes the composite electrode sheet 20 and the isolation membrane 310 in the above embodiment. The battery cell 30 including the composite electrode sheet 20 in the above embodiment acts as an isolation membrane because the composite current collector 10 isolates the positive electrode material layer 210 and the negative electrode material layer 220; and the ions in the electrolyte can pass through the composite current collector 10 and move between the positive electrode material layer 210 and the negative electrode material layer 220. The structure of the above battery cell 30 is simple, the internal resistance of the battery cell 30 is small, and the positive electrode and the negative electrode are integrated into one, the volume of the battery cell 30 is smaller, and the energy density is higher.
[0094] The present application has no particular limitation on the type of the isolation membrane 310 , and any known porous structure isolation membrane 310 with good chemical stability and mechanical stability can be selected.
[0095] In some embodiments, the material of the isolation film 310 can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation film 310 can be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation film 310 is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.
[0096] In some embodiments, the battery cell 30 can be obtained by a winding process or a lamination process. By winding or laminating the composite electrode 20 and the isolation film 310 to obtain the battery cell 30, compared with the traditional battery cell, on the one hand, the amount of isolation film 310 is reduced, and the unit volume of the wound battery cell 30 is reduced; on the other hand, the preparation process of the battery cell 30 is also simplified.
[0097] Another embodiment of the present application also provides a battery cell, which includes: a housing and at least one battery cell 30 in the above embodiment. The battery cell in the technical solution of this embodiment includes at least one battery cell 30 in the above embodiment, and the energy density of the battery cell is higher, which can meet higher usage requirements.
[0098] See also Figure 6 , Figure 6 The schematic diagram of the exploded structure of the battery cell 40 provided in some embodiments of the present application. The battery cell 40 refers to the smallest unit that constitutes the battery. Figure 6 The battery cell 40 includes an end cover 41 , a shell 42 and a battery cell 30 .
[0099] The end cap 41 refers to a component that covers the opening of the shell 42 to isolate the internal environment of the battery cell 40 from the external environment. Without limitation, the shape of the end cap 41 can be adapted to the shape of the shell 42 to match the shell 42. Optionally, the end cap 41 can be made of a material with a certain hardness and strength (such as aluminum alloy), so that the end cap 41 is not easily deformed when squeezed and collided, so that the battery cell 40 can have a higher structural strength and the safety performance can also be improved. Functional components such as electrode terminals 41a can be provided on the end cap 41. The electrode terminal 41a can be used to electrically connect to the battery cell 30 for outputting or inputting electrical energy of the battery cell 40. In some embodiments, the end cap 41 can also be provided with a pressure relief mechanism for releasing the internal pressure when the internal pressure or temperature of the battery cell 40 reaches a threshold. The material of the end cap 41 can also be a variety of materials, such as copper, iron, aluminum, stainless steel, aluminum alloy, plastic, etc., and the embodiment of the present application does not impose any special restrictions on this. In some embodiments, an insulating member may be provided inside the end cap 41, and the insulating member may be used to isolate the electrical connection components in the housing 42 from the end cap 41 to reduce the risk of short circuit. For example, the insulating member may be plastic, rubber, or the like.
[0100] The shell 42 is a component used to cooperate with the end cover 41 to form the internal environment of the battery cell 40, wherein the formed internal environment can be used to accommodate the battery cell 30, the electrolyte (not shown in the figure) and other components. The shell 42 and the end cover 41 can be independent components, and an opening can be set on the shell 42, and the internal environment of the battery cell 40 is formed by covering the opening with the end cover 41 at the opening. Without limitation, the end cover 41 and the shell 42 can also be integrated. Specifically, the end cover 41 and the shell 42 can form a common connection surface before other components are put into the shell, and when the interior of the shell 42 needs to be encapsulated, the end cover 41 covers the shell 42. The shell 42 can be of various shapes and sizes, such as a rectangular parallelepiped, a cylindrical shape, a hexagonal prism, etc. Specifically, the shape of the shell 42 can be determined according to the specific shape and size of the battery cell 30. The material of the shell 42 can be various, such as copper, iron, aluminum, stainless steel, aluminum alloy, plastic, etc., and the embodiment of the present application does not impose any special restrictions on this.
[0101] The electrolyte includes an electrolyte salt and a solvent. In some embodiments, the electrolyte salt can be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate, and lithium tetrafluorooxalatophosphate.
[0102] In some embodiments, the solvent can be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane sulfone, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.
[0103] In some embodiments, the electrolyte may further optionally include additives.
[0104] Another embodiment of the present application provides a battery, including: the battery cell in the above embodiment.
[0105] See also Figure 7 , Figure 7 A schematic diagram of the exploded structure of a battery 50 provided for some embodiments of the present application. The battery 50 includes a box 51 and a battery cell 40, and the battery cell 40 is contained in the box 51. Among them, the box 51 is used to provide a storage space for the battery cell 40, and the box 51 can adopt a variety of structures. In some embodiments, the box 51 may include a first part 511 and a second part 512, and the first part 511 and the second part 512 cover each other, and the first part 511 and the second part 512 jointly define a storage space for accommodating the battery cell 40. The second part 512 can be a hollow structure with one end open, and the first part 511 can be a plate-like structure, and the first part 511 covers the open side of the second part 512, so that the first part 511 and the second part 512 jointly define a storage space; the first part 511 and the second part 512 can also be hollow structures with one side open, and the open side of the first part 511 covers the open side of the second part 512. Of course, the box formed by the first part 511 and the second part 512 can be in various shapes, such as a cylinder, a cuboid, etc.
[0106] In the battery 50, there can be multiple battery cells 40, and the multiple battery cells 40 can be connected in series, in parallel, or in a mixed connection. A mixed connection means that the multiple battery cells are both connected in series and in parallel. The multiple battery cells 40 can be directly connected in series, in parallel, or in a mixed connection, and then the whole formed by the multiple battery cells 40 is accommodated in the box 51; of course, the battery 50 can also be a battery module formed by connecting multiple battery cells 40 in series, in parallel, or in a mixed connection, and then the multiple battery modules are connected in series, in parallel, or in a mixed connection to form a whole, and accommodated in the box 51. The battery 50 can also include other structures. For example, the battery 50 can also include a converging component for realizing electrical connection between the multiple battery cells 40.
[0107] Another embodiment of the present application further provides an electric device, including the battery in the above embodiment. The electric device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but is not limited thereto.
[0108] See also Figure 8 , Figure 8 A schematic diagram of the structure of a vehicle 60 provided for some embodiments of the present application. The vehicle 60 may be a fuel vehicle, a gas vehicle or a new energy vehicle, and the new energy vehicle may be a pure electric vehicle, a hybrid vehicle or an extended-range vehicle, etc. A battery 50 is provided inside the vehicle 60, and the battery 50 may be provided at the bottom, the head or the tail of the vehicle 60. The battery 50 may be used to power the vehicle 60, for example, the battery 50 may be used as an operating power source for the vehicle 60. The vehicle 60 may also include a controller 61 and a motor 62, and the controller 61 is used to control the battery 50 to power the motor 62, for example, for starting, navigating and driving the vehicle 60.
[0109] In some embodiments of the present application, the battery 50 can not only serve as an operating power source for the vehicle 60 , but also serve as a driving power source for the vehicle 60 , replacing or partially replacing fuel or natural gas to provide driving power for the vehicle 60 .
[0110] As another example, the device may be a mobile phone, a tablet computer, a laptop computer, etc.
[0111] The present application is further described below through specific embodiments.
[0112] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.
[0113] Preparation of composite current collector:
[0114] The conductive layer is prepared by vacuum evaporation, and the porosity of the conductive layer is controlled by setting a mask with a porous structure as a template during the evaporation process.
[0115] A polymer support layer with a specific air permeability is taken and surface cleaned, and then the surface cleaned polymer support layer is placed in a vacuum plating chamber. The high-purity copper wire in the metal evaporation chamber is melted and evaporated at a high temperature of 1300°C to 2000°C. The evaporated metal passes through a cooling system in the vacuum plating chamber and is finally deposited on one side of the polymer support layer to form a copper-based negative electrode conductive layer.
[0116] A polymer support layer plated with a copper-based negative electrode conductive layer is placed in a vacuum plating chamber, and the high-purity aluminum wire in the metal evaporation chamber is melted and evaporated at a high temperature of 1300°C to 2000°C. The evaporated metal passes through a cooling system in the vacuum plating chamber and is finally deposited on the surface of the polymer support layer away from the negative electrode conductive layer to form an aluminum-based positive electrode conductive layer.
[0117] Preparation of composite pole piece:
[0118] The positive electrode active material LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O 2 (NCM333), conductive carbon black and binder polyvinylidene fluoride (PVDF) are fully stirred and mixed in a proper amount of N-methylpyrrolidone (NMP) solvent in a mass ratio of 93:2:5 to form a uniform positive electrode slurry; the positive electrode slurry is coated on the surface of the positive electrode conductive layer of the composite current collector, and after drying and other processes, a positive electrode material layer is obtained.
[0119] The negative electrode active material graphite, conductive carbon black, thickener sodium carboxymethyl cellulose (CMC) and binder styrene butadiene rubber latex (SBR) are fully stirred and mixed in a proper amount of deionized water at a mass ratio of 96.5:1.0:1.0:1.5 to form a uniform negative electrode slurry; the negative electrode slurry is coated on the surface of the negative electrode conductive layer of the composite current collector, and after drying and other processes, a negative electrode material layer is obtained. In this way, a composite electrode sheet is obtained.
[0120] Preparation of lithium-ion secondary batteries:
[0121] The prepared composite pole piece and the isolation film are stacked and wound to form a battery cell, which is then placed in a packaging shell, and an electrolyte is injected into the battery cell and sealed to obtain a lithium-ion secondary battery.
[0122] The structural parameters of the composite current collectors in Examples 1 to 12 and Comparative Examples 1 to 3 can be found in Table 1.
[0123] Specifically, the air permeability of the polymer support layer was measured using a Japanese KRK Wangyan air permeability tester 0518-P. The test parameters are: smoothness measurement area 8.08 square centimeters; smoothness measurement load 8.08 kilograms; total length of the measuring wheel 733mm; area for measuring air permeability 645.16mm² (1.00in2); measurement range (nozzle switching): smoothness center value 100, 500, 1000 seconds, air permeability center value 100, 500, 1000, 2000 seconds; electronic pressure gauge capacity 1,000 mmH 2 OReference air pressure 500 mmH 2 O 3-level pressure adjustment; timer 3-digit display (seconds); power supply 100 / 110V 50 / 60Hz 1A; gas source: 0.5MPa. The porosity of the conductive layer is monitored by CCD during the preparation process to calculate the pore occupancy per unit area, i.e., the porosity.
[0124] Table 1
[0125]
[0126] Embodiment 1:
[0127] In this embodiment, the polymer support layer of the composite current collector is a PE film with an air permeability of 50 s / 100cc.
[0128] The porosity of the positive electrode conductive layer and the negative electrode conductive layer are both 10%, and the thickness is both 200 nm.
[0129] Embodiment 2:
[0130] In this embodiment, the polymer support layer of the composite current collector is a PE film with an air permeability of 1500 s / 100cc.
[0131] The porosity of the positive electrode conductive layer and the negative electrode conductive layer are both 50%, and the thickness is both 1000 nm.
[0132] Embodiment 3:
[0133] In this embodiment, the polymer support layer of the composite current collector is a PE film with an air permeability of 3000 s / 100cc.
[0134] The porosity of the positive electrode conductive layer and the negative electrode conductive layer are both 95%, and the thickness is both 3000 nm.
[0135] Embodiment 4:
[0136] In this embodiment, the polymer support layer of the composite current collector is a PE film with an air permeability of 300 s / 100cc.
[0137] The porosity of the positive electrode conductive layer and the negative electrode conductive layer are both 3%, and the thickness is both 500 nm.
[0138] Embodiment 5:
[0139] In this embodiment, the polymer support layer of the composite current collector is a PE film with an air permeability of 150 s / 100cc.
[0140] The porosity of the positive electrode conductive layer and the negative electrode conductive layer are both 60%, and the thickness is both 1500 nm.
[0141] Embodiment 6:
[0142] The composite current collector of this embodiment is substantially the same as the composite current collector of Embodiment 2, except that, in this embodiment, the thickness of the positive electrode conductive layer and the negative electrode conductive layer are both 100 nm.
[0143] Embodiment 7:
[0144] The composite current collector of this embodiment is substantially the same as the composite current collector of Embodiment 2, except that, in this embodiment, the thickness of the positive electrode conductive layer and the negative electrode conductive layer are both 4000 nm.
[0145] In the above-mentioned Examples 1 to 7, the conductive layer only includes the functional layer.
[0146] Embodiment 8:
[0147] The composite current collector of this embodiment is substantially the same as the composite current collector of Embodiment 2, except that a PI film having an air permeability of 1500 s / 100cc is used as the polymer support layer.
[0148] Embodiment 9:
[0149] The composite current collector of this embodiment is substantially the same as the composite current collector of Embodiment 2, except that a PET film having an air permeability of 1500 s / 100cc is used as the polymer support layer.
[0150] Embodiment 10:
[0151] The composite current collector of this embodiment is basically the same as the composite current collector in Example 2, except that the conductive layer includes a pore-making transition layer and a functional layer, the thickness of the pore-making transition layer is 100 nm, and the thickness of the functional layer is 900 nm. The preparation method of the conductive layer is different: first, the pore-making transition layer is prepared by the above-mentioned vacuum evaporation method, and the porosity of the pore-making transition layer is controlled by setting a mask with a porous structure as a template during the evaporation process. Then, the prepared pore-making transition layer is immersed in an electroplating tank containing a metal ion plating solution, and the metal ions are reduced and deposited under the action of current to form a functional layer. Both the positive electrode conductive layer and the negative electrode conductive layer are prepared by the above method.
[0152] Embodiment 11:
[0153] The composite current collector of this embodiment is basically the same as the composite current collector in Example 2, except that the conductive layer includes a thickening layer and a functional layer, the thickness of the thickening layer is 100 nm, and the thickness of the functional layer is 900 nm. The thickening layer and the functional layer of the conductive layer are both prepared by the above-mentioned vacuum evaporation method.
[0154] Embodiment 12:
[0155] The composite current collector of this embodiment is basically the same as the composite current collector in Example 2, except that the surface of the positive electrode conductive layer and the negative electrode conductive layer is also covered with an anti-oxidation layer, the material of the anti-oxidation layer is metal Cr, the thickness is 500 nm, and it is prepared by electroplating.
[0156] Comparative Example 1:
[0157] The composite current collector of this comparative example is substantially the same as the composite current collector of Example 2, except that, in this comparative example, a PE film with an air permeability of 10 s / 100cc is selected as the polymer support layer.
[0158] Comparative Example 2:
[0159] The composite current collector of this comparative example is substantially the same as the composite current collector of Example 2, except that, in this comparative example, the porosity of the positive electrode conductive layer and the negative electrode conductive layer are both 0.
[0160] Comparative Example 3:
[0161] The composite current collector of this comparative example is substantially the same as the composite current collector of Example 2, except that, in this comparative example, a PE film with an air permeability of 3500 s / 100cc is selected as the polymer support layer.
[0162] test:
[0163] Electrochemical performance tests were performed on the lithium-ion secondary batteries prepared in Examples 1 to 12 and Comparative Examples 1 to 3. Please refer to Table 2 for the test results.
[0164] Specifically, the internal resistance of the lithium-ion secondary battery is measured by a battery internal resistance tester (ATS21 model of Amber Company). After the probes of the battery internal resistance tester are clamped on the two side poles of the lithium-ion secondary battery for 5 seconds, the resistance value is read after the reading of the tester is stable.
[0165] Discharge energy density detection:
[0166] (1) Energy density at 0.1C discharge (Wh / kg)
[0167] The lithium-ion secondary battery was placed at room temperature for 30 minutes, and then charged at a constant current of 0.05C charging rate to a voltage of 4.4V, and then discharged at a rate of 0.05C to 3.0V, and the above charging and discharging steps were repeated for 3 cycles to complete the formation of the lithium-ion secondary battery. The battery was charged at a constant current of 0.1C charging rate to a voltage of 4.4V, and then discharged at a discharge rate of 0.1C to 3.0V, and its discharge capacity was recorded, and then the energy density at 0.1C discharge was calculated.
[0168] Energy density (Wh / kg) = discharge capacity (Wh) / mass of lithium-ion secondary battery (kg)
[0169] (2) Energy density at 2C discharge (Wh / kg)
[0170] The lithium-ion secondary battery was placed at room temperature for 30 minutes, and then charged at a constant current of 0.05C charging rate to a voltage of 4.4V, and then discharged at a rate of 0.05C to 3.0V, and the above charging and discharging steps were repeated for 3 cycles to complete the formation of the lithium-ion secondary battery. The battery was charged at a constant current of 2C charging rate to a voltage of 4.4V, and then discharged at a discharge rate of 2C to 3.0V, and its discharge capacity was recorded, and then the energy density of the 2C device during discharge was calculated.
[0171] Energy density (Wh / kg) = discharge capacity (Wh) / mass of lithium-ion secondary battery (kg)
[0172] Cycle performance test:
[0173] In a 25°C environment, the lithium-ion secondary battery is charged and discharged for the first time. It is charged at a constant current of 1C, then charged at a constant voltage until the voltage reaches 4.2V, and then discharged at a constant current of 1C until the final voltage reaches 2.8V. The discharge capacity of the first cycle is recorded. Then the charge and discharge cycle is repeated, and the discharge capacity of the 1000th cycle is recorded.
[0174] Capacity retention rate = (discharge capacity at the last 1000 cycles / discharge capacity at the first cycle) × 100%
[0175] Table 2 Electrochemical properties of lithium ion secondary batteries of Examples 1 to 12 and Comparative Examples 1 to 3
[0176]
[0177] From the data in Table 2, it can be seen that compared with the lithium ion secondary batteries prepared in Comparative Examples 1 to 3, the lithium ion secondary batteries prepared in Examples 1 to 12 have lower internal resistance, between 0.4 mΩ and 0.7 mΩ; higher energy density, 130 Wh / kg to 320 Wh / kg at 0.1C discharge, and 104 Wh / kg to 304 Wh / kg at 2C discharge; and better cycle performance, with a capacity retention rate of 70% to 96% after 1,000 cycles. In particular, the lithium ion secondary batteries prepared in Examples 2, 4, and 5 have both lower internal resistance of lithium ion secondary batteries and higher energy density and capacity retention rate.
[0178] Compared with Example 2, the thickness of the conductive layer of the composite current collector in the lithium ion secondary battery prepared in Example 6 is 100 nm, and the thickness of the conductive layer of the composite current collector in the lithium ion secondary battery prepared in Example 7 is 4000 nm. The internal resistance of the lithium ion secondary batteries of Examples 6 and 7 increased, and the energy density decreased significantly. The capacity retention rates after 1000 cycles were 70% and 75%, respectively. It can be seen that the thickness of the conductive layer in the composite current collector is too large or too small, which is not conducive to reducing the internal resistance of the battery and improving the energy density. The thickness of the conductive layer is more suitable in the range of 200 nm to 3000 nm. In addition, the capacity retention rate of the lithium ion secondary battery in Example 6 is significantly reduced due to the small thickness of the conductive layer of the composite current collector, indicating that the thickness of the conductive layer is too small, which is not conducive to improving the battery cycle stability.
[0179] Compared with Example 2, the materials of the polymer support layers in Examples 8 and 9 are different, and the performances of the prepared lithium-ion secondary batteries are close to those in Example 2.
[0180] Compared with Example 2, the structure or preparation method of the conductive layer in Examples 10 and 11 is slightly different, and the internal resistance of the prepared lithium ion secondary battery is slightly higher than that of the lithium ion secondary battery in Example 2.
[0181] The composite current collector of the lithium ion secondary battery of Example 12 is based on Example 2, and an anti-oxidation layer is further provided on the surface of the conductive layer. Compared with Example 2, the internal resistance of the lithium ion secondary battery prepared in Example 12 is increased, the energy density is reduced, and the cycle stability performance is slightly improved.
[0182] Compared with Example 2, the air permeability of the polymer support layer of the composite current collector in the lithium ion secondary battery prepared in Comparative Example 1 is 10 s / 100cc, the internal resistance of the lithium ion secondary battery in Comparative Example 1 is significantly increased, the energy density is reduced, and the capacity retention rate after 1000 cycles is only 60%. The air permeability of the polymer support layer of the composite current collector in the lithium ion secondary battery prepared in Comparative Example 3 is 3500 s / 100cc, the internal resistance of the lithium ion secondary battery in Comparative Example 3 is significantly increased, the energy density is reduced, and the capacity retention rate after 1000 cycles is only 80%. This shows that the air permeability of the polymer support layer of the composite current collector will significantly affect the internal resistance, energy density and capacity retention rate of the lithium ion secondary battery, and too large or too small will affect the electrochemical performance of the lithium ion secondary battery.
[0183] Compared with Example 2, the porosity of the conductive layer of the composite current collector in the lithium ion secondary battery prepared in Comparative Example 2 is 0, the internal resistance of the lithium ion secondary battery in Comparative Example 1 is significantly increased, the energy density is reduced, and the capacity retention rate after 1000 cycles is only 65%. This shows that the composite current collector with a conductive layer of a specific porosity is conducive to reducing the internal resistance of the lithium ion secondary battery, and is also conducive to improving the battery energy density and cycle stability.
[0184] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0185] The above-described embodiments only express several implementation methods of the present application, which is convenient for understanding the technical solutions of the present application in detail, but cannot be understood as limiting the scope of protection of the invention patent. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present application, which all belong to the protection scope of the present application. It should be understood that the technical solutions obtained by those skilled in the art through logical analysis, reasoning or limited experiments on the basis of the technical solutions provided in the present application are all within the protection scope of the claims described in the present application. Therefore, the scope of protection of the patent of this application shall be based on the contents of the attached claims, and the description and drawings may be used to interpret the contents of the claims.
Claims
1. A composite current collector, characterized in that: include: A polymer support layer, wherein the air permeability of the polymer support layer is 50 s / 100cc to 3000 s / 100cc; and A conductive layer, wherein the conductive layer includes a negative electrode conductive layer and a positive electrode conductive layer; The negative electrode conductive layer and the positive electrode conductive layer are respectively disposed on both side surfaces of the polymer support layer; the porosity of the negative electrode conductive layer and the positive electrode conductive layer are independently 10% to 95%; The material of the conductive layer is selected from at least one of a metal material, a carbon-based conductive material and a polymer conductive material; the thickness of the negative electrode conductive layer is 200 nm to 3000 nm, and the thickness of the positive electrode conductive layer is 200 nm to 3000 nm.
2. The composite current collector according to claim 1, characterized in that: The air permeability of the polymer support layer is 150 s / 100 cc to 1500 s / 100 cc.
3. The composite current collector according to claim 1 or 2, characterized in that: The porosity of the negative electrode conductive layer and the positive electrode conductive layer is independently 30% to 60%.
4. The composite current collector according to claim 1 or 2, characterized in that: The thickness of the negative electrode conductive layer is 500nm~1500nm; And / or, the thickness of the positive electrode conductive layer is 500 nm to 1500 nm.
5. The composite current collector according to claim 1 or 2, characterized in that: The negative electrode conductive layer and / or the positive electrode conductive layer comprises: a functional layer; the thickness of the functional layer is 500 nm to 3000 nm.
6. The composite current collector according to claim 5, characterized in that: The negative electrode conductive layer and / or the positive electrode conductive layer further comprises: at least one of a pore-forming transition layer and a thickening layer; The thickness of the hole-making transition layer is 2 nm to 100 nm; the thickness of the thickening layer is 5 nm to 300 nm.
7. The composite current collector according to any one of claims 1, 2 and 6, characterized in that: The composite current collector further comprises: An anti-oxidation layer is disposed on a surface of the negative electrode conductive layer and / or the positive electrode conductive layer away from the polymer support layer.
8. The composite current collector according to claim 7, characterized in that: The material of the anti-oxidation layer is selected from at least one of conductive carbon, metal material and metal oxide.
9. The composite current collector according to claim 7, characterized in that: The thickness of the anti-oxidation layer is 500 nm to 1500 nm.
10. The composite current collector according to any one of claims 1, 2, 6, 8 and 9, characterized in that: The material of the polymer support layer is selected from at least one of polyamide, polyimide, polyethylene terephthalate, polyethylene, polypropylene, polyvinyl alcohol, polystyrene and cellulose.
11. A composite pole piece, characterized in that: include: The composite current collector according to any one of claims 1 to 10; A positive electrode material layer, the positive electrode material layer is disposed on a surface of the positive electrode conductive layer away from the polymer support layer; and A negative electrode material layer is provided on a surface of the negative electrode conductive layer away from the polymer support layer.
12. A battery cell, characterized in that: include: The composite pole piece according to claim 11, and Isolation film; The battery core is manufactured by a winding process or a lamination process.
13. A battery cell, characterized in that: include: A housing and at least one battery cell as claimed in claim 12.
14. A battery, characterized in that: include: The battery cell as claimed in claim 13.
15. An electrical device, characterized in that: Comprising the battery of claim 14.
Citation Information
Cited By
Positive electrode composite current collector, battery monomer, battery device and electric device
CN120048908A
Positive composite current collector, battery cell, battery device, and electrical device
CN120048908B
Battery cell, battery apparatus, and electric device
WO2026149198A1
